2020
DOI: 10.1002/ajmg.a.61848
|View full text |Cite
|
Sign up to set email alerts
|

Novel NEXMIF gene pathogenic variant in a female patient with refractory epilepsy and intellectual disability

Abstract: We identified a novel nonsense de novo pathogenic variant of the NEXMIF gene in a 29 year-old female patient with refractory epilepsy and mild intellectual disability. The patient presented with episodic atypical absence status (AS), the longest duration of her seizures was approximately 36 hr. She also had occasional eyelid myoclonia during absence seizure. EEG highlighted a photosensitivity phenomenon and generalized epileptiform discharges that were induced by eye closure. Whole exome sequencing revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Finally, two more female patients with alterations in the NEXMIF gene and a phenotype resembling EMA have been reported. Wu et al (2020) described a woman with refractory epilepsy and EEG features similar to those described in EMA who was a carrier of a nonsense variant in NEXMIF (p.Leu355*) ( Table 2 ) [ 43 ]. Samanta and Willis (2020) identified a frameshift mutation (p.Asp573Serfs*11) in a girl with intractable seizures diagnosed with EMA [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, two more female patients with alterations in the NEXMIF gene and a phenotype resembling EMA have been reported. Wu et al (2020) described a woman with refractory epilepsy and EEG features similar to those described in EMA who was a carrier of a nonsense variant in NEXMIF (p.Leu355*) ( Table 2 ) [ 43 ]. Samanta and Willis (2020) identified a frameshift mutation (p.Asp573Serfs*11) in a girl with intractable seizures diagnosed with EMA [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using NGS, Ittiwut et al [88] identified a de novo variant (c.467A>T) in ATP6V0C in a patient with intractable epilepsy and intellectual disability, which was a conserved termination codon mutation. Meanwhile, Wu et al suggested that NEXMIF with X-inactivation patterns might have contributed to the mild intellectual disability [89].…”
Section: Epilepsymentioning
confidence: 99%
“…The reported individuals with NEXMIF -dependent ASD show impaired communication, repetitive behaviors, seizures, ID, and microcephaly. Interestingly, although only male cases were reported in earlier studies, recent clinical reports indicate that autistic characteristics are also observed in females with NEXMIF mutations [ [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Due to infertility of affected males, females with inherited NEXMIF mutations are heterozygous and therefore haploinsufficient in NEXMIF.…”
Section: Introductionmentioning
confidence: 99%